A Comparative Study of Esketamine-Propofol and Sufentanil-Propofol for Analgesia and Sedation During Breast Minimally Invasive Rotary Resection with Local Anesthesia: A Randomized Double-Blind Clinical Trial - Li N; Qi X; Bao J; Gu Y; Zhou X; Wang T; Jiang N; Wang Y; Ye Q (Drug Design, Development and Therapy)
Ningkang Li,1,2,* Xia Qi,2,* Jiamin Bao,2 Yang Gu,1,2 Xiaohong Zhou,1,2 Ting Wang,2 Ningxiang Jiang,3 Yun Wang,2 Qingshan Ye1,2 1Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 2Department of Anesthesiology, People’s Hospital of Ningxia Hui Autonomous Region, Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 3Department of Breast Surgery, People’s Hospital of Ningxia Hui Autonomous Region, Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingshan Ye; Yun Wang, Department of Anesthesiology, People’s Hospital of Ningxia Hui Autonomous Region, Yinchuan, Ningxia, 750002, People’s Republic of China, Email yeqingshan@hotmail.com; wangyun10483@126.comPurpose: Minimally invasive rotary resection (MIRR) is crucial for diagnosing and treating breast tumors, but the optimal intravenous anesthesia regimen is unclear. Esketamine, an NMDA receptor antagonist with anesthetic, analgesic, and sympathomimetic properties, may provide an ideal adjunct to propofol sedation. This study aims to compare the safety and efficacy of esketamine versus sufentanil as adjuncts to propofol for analgesia and sedation during breast MIRR.Patients and Methods: A total of 90 patients undergoing elective breast MIRR were randomly assigned to receive either sufentanil-propofol or esketamine-propofol for analgesia and sedation. The primary outcome was the occurrence of hypoxia (SpO2 < 92% for > 10s or exhibiting a persistent downward trajectory). Other outcomes included incidence of subclinical respiratory depression (92% ≤ SpO2 < 95% for > 10s), number of airway interventions, awakening time, satisfaction scores, postoperative exhaust time, hemodynamic parameters, and side events.Results: Finally, 41 patients were assigned to the sufentanil group and 40 to the esketamine group. The occurrence of hypoxia was significantly lower in the esketamine group (17.5%) than in the sufentanil group (39%) (P = 0.032). Subclinical respiratory depression occurred in 32.5% of the esketamine group and 56.1% of the sufentanil group (P = 0.033). The sufentanil group required more airway interventions than the esketamine group (P = 0.032), and patients in the sufentanil group experiencing hypoxia received more mask-assisted ventilation (P = 0.029). Hemodynamic stability was better in the esketamine group. No significant differences were observed in awakening time, satisfaction score, postoperative exhaust time, or side events between groups.Conclusion: Esketamine-propofol anesthesia significantly reduces the risk of hypoxia (SpO2 < 92%) compared to sufentanil-propofol, while maintaining similar awakening time, satisfaction, postoperative exhaust time, and side events. Its hemodynamic advantages make it valuable for clinical use, especially in procedures requiring respiratory and hemodynamic stability.Keywords: esketamine, hypoxia, respiratory depression, minimally invasive rotary resection, breast tumor